1988
DOI: 10.1002/ajpa.1330750105
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin (GM and KM) allotypes in the Sikh population of India

Abstract: The populations of India are genetically diverse, both within and between geographic regions; immunoglobulin (GM) allotypes provide important information on genetic differences between populations, since the frequencies of combinations of allotypes (termed "haplotypes") vary dramatically among ethnic groups. As part of a project to assess genetic diversity among defined Indian populations, we have examined eight GM allotypes in a sample of 101 unrelated Sikhs who have migrated to Toronto, Canada: Glm(1, 2, 3, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Sikhs or Muslims) is either very low or they are even completely absent. This follows from studies on Punjabis (Daveau et al, 1980), higher and lower caste Hindus from Northwest India (Schanfield and Kirk, 1981), upper-caste Hindus from Bengal (Ray and Field, 1981), Sikhs (Field et al, 1988), and Brahmins, Kalitas, Kaibartas, and Muslims from Assam (Walter et al, 1987). All these population groups are characterized by the clear prevalence of the "Caucasoid" array of GM haplotypes, namely GM'1,17;21,26;GM* 1,2,17;21,26;and GM'3;5,10,11,13,14,26.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Sikhs or Muslims) is either very low or they are even completely absent. This follows from studies on Punjabis (Daveau et al, 1980), higher and lower caste Hindus from Northwest India (Schanfield and Kirk, 1981), upper-caste Hindus from Bengal (Ray and Field, 1981), Sikhs (Field et al, 1988), and Brahmins, Kalitas, Kaibartas, and Muslims from Assam (Walter et al, 1987). All these population groups are characterized by the clear prevalence of the "Caucasoid" array of GM haplotypes, namely GM'1,17;21,26;GM* 1,2,17;21,26;and GM'3;5,10,11,13,14,26.…”
Section: Resultsmentioning
confidence: 99%
“…Concerning the occurrence of "Mongoloid" GM haplotypes in the Assamese caste and community populations Walter et al (1987) suggested some gene flow from Mongoloid side, which could be substantiated considering the ethnohistory of Assam. The occurrence of "Mongoloid" haplotypes in Sikhs was explained by the possibility, that they may have characteristic of some of the Hindu castes in the Punjab, from which the Sikhs are descended (Field et al, 1988).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Asia, however, especially in the northeastern parts of India (Assam), this Mongoloid haplotype was also found among several populations of Caucasoid origin, which suggests that some genetic contact with Mongoloid populations living there had taken place . Field et al (1988) observed this haplotype in a Sikh sample (from Canada, but originating from Northwest India). This suggests a larger distribution of this Mongoloid haplotype in Asia than so far supposed, and its actual distribution especially in Western Asia including the Middle East should be more thoroughly reviewed therefore.…”
Section: Methodsmentioning
confidence: 91%